-2(7w-2)+2w=2(w+1)

Simple and best practice solution for -2(7w-2)+2w=2(w+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(7w-2)+2w=2(w+1) equation:


Simplifying
-2(7w + -2) + 2w = 2(w + 1)

Reorder the terms:
-2(-2 + 7w) + 2w = 2(w + 1)
(-2 * -2 + 7w * -2) + 2w = 2(w + 1)
(4 + -14w) + 2w = 2(w + 1)

Combine like terms: -14w + 2w = -12w
4 + -12w = 2(w + 1)

Reorder the terms:
4 + -12w = 2(1 + w)
4 + -12w = (1 * 2 + w * 2)
4 + -12w = (2 + 2w)

Solving
4 + -12w = 2 + 2w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-2w' to each side of the equation.
4 + -12w + -2w = 2 + 2w + -2w

Combine like terms: -12w + -2w = -14w
4 + -14w = 2 + 2w + -2w

Combine like terms: 2w + -2w = 0
4 + -14w = 2 + 0
4 + -14w = 2

Add '-4' to each side of the equation.
4 + -4 + -14w = 2 + -4

Combine like terms: 4 + -4 = 0
0 + -14w = 2 + -4
-14w = 2 + -4

Combine like terms: 2 + -4 = -2
-14w = -2

Divide each side by '-14'.
w = 0.1428571429

Simplifying
w = 0.1428571429

See similar equations:

| -5+4x=27 | | F=8/5(n-56) | | -6x+3=-57 | | 265+48r=553 | | 2x/3+4=x-3/5 | | -1/3=-3/2v-3/4 | | 5x+4x-27=18 | | 0.04(y-7)+0.06y=0.20y-0.05(20) | | 3/2x-1/5=-5/7 | | 4/x=3 | | 7(y+3)=5y+3 | | 7/6+6=-8 | | 14x^2-7=0 | | -4v-37=3(v+4) | | 6r-8-2r=-16 | | -2(14-3x)=7x+2x | | (1/2)-(5/8)x=(7/8)x-(7/2) | | 12n^2-16n+5=0 | | 3(x+8)=5(x-10) | | y^3-7y^2+4y+12=0 | | y/9-6=5 | | 9m+6n-9(8m-5n)= | | 0.7m-3.2=2.5+1.5m | | C-6y= | | -3+5x=-12 | | 2x/3+5/6+x/2=7 | | 26c-(10c-75)= | | 1/5(4x+64)=4x | | 8m-4m-6-3+5m=8.2-1 | | 23-t=-10 | | y/10+5=-18 | | -11x+38=16 |

Equations solver categories